INTERNATIONAL AND NATIONAL PROGRAMMES TO ASSIST WAR-AFFECTED PEOPLE: CHALLENGES AND PROSPECTS - YERMAK, OLEKSANDR; MYROSHNYCHENKO, ALINA (Ehrlich's Journal, 2025)
The article examines the current state of international and national programmes of assistance to war victims as an important element of humanitarian policy. In the context of the armed conflict that has been ongoing in Ukraine since 2014 and escalated in 2022, the issue of the effectiveness of such programmes is of particular relevance. This paper analyses the main mechanisms of support for victims, including the provision of financial, humanitarian, social and psychological assistance. Particular attention is paid to international organisations such as the United Nations High Commissioner for Refugees (UNHCR), UNICEF and the United Nations Development Programme (UNDP), which provide a significant part of humanitarian assistance in Ukraine. The author analyses their activities, main programmes and the scope of support, including multi-purpose cash assistance, restoration of social infrastructure, support for children and families affected by the war. The key problems of implementing international programmes are highlighted, including bureaucratic obstacles, insufficient funding and difficulties with coordination between different structures. National assistance programmes, such as ePidtryadka, charitable organisations (Caritas Ukraine) and mental health initiatives, also play an important role in providing assistance to victims. The main challenges facing national initiatives are identified, including insufficient funding, uneven access to resources and the need for long-term rehabilitation measures. The article emphasises the need to increase the effectiveness of international and national assistance programmes by strengthening coordination between international agencies and the government, increasing funding for national initiatives, developing long-term programmes for socio-economic integration and expanding access to psychological and medical support. The study findings show that the integration of international experience with local capacities is a key factor in effective support for war-affected people. Optimisation of assistance mechanisms will not only meet the basic needs of the population, but will also contribute to the sustainable recovery of Ukraine in the postconflict period.